Cutaneous lymphangitic carcinomatosis from cervical cancer - Daniel Barquero‐Orias; Nelson Aguilar‐Aguilar; Camila Martin‐Zamora; Maria F. Vargas‐Wille; Daniel Gutiérrez‐Araya; Rodolfo Suarez‐Monge (Wiley, 2024)
Abstract We report a case of cutaneous lymphangitic carcinomatosis arising from cervical cancer in a 66‐year‐old woman. No standardized treatment protocol currently exists for cutaneous lymphangitic carcinomatosis; in our case, treatment with carboplatin and paclitaxel induced a positive clinical skin response, but the patient passed away from metastatic disease.